Formaldehyde-free adhesive as well as preparation method and application thereof
By using a dextile-free adhesive composed of flowing agent and filler reacts with biomass fibers to form covalent bonds, the problem of insufficient anti-aldehyde-free adhesive in existing artificial boards is solved, and high-strength bonding and stable chemical properties are achieved Effect.
Patent Information
- Application Number
- CN202411567009.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The adhesives in existing artificial boards are not well-free and environmentally friendly, resulting in environmental pollution and limited application.
The aldehyde-free adhesive composed of a flowing agent and a filler is used. The epoxy group in the flowing agent and the carboxyl or anhydride group in the filler are reacted with the biomass fibers at high temperature to form a covalent bond and achieve bonding.
High-strength bonding is achieved, and the chemical properties of the aldehyde-free adhesive are stable, not easy to deteriorate, avoid formaldehyde release, and meet the needs of environmental protection and efficient utilization.
Smart Images

Figure CN119432282A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of artificial board manufacturing, and particularly relates to a formaldehyde-free adhesive and a preparation method and application thereof. Background Art
[0002] Artificial boards are made of wood or other non-wood plants as the base material, which are separated into various unit materials through certain mechanical processing, and then pressed together with a certain amount of adhesives and other additives. my country's forestry resources are limited, and the growth cycle of trees is long. The output of logs is far from meeting the demand for boards in the fields of construction and home decoration. Artificial boards can use branches, shrubs, bamboo and reeds, and even agricultural and forestry residues or by-products such as sawdust, straw, and sugarcane bagasse as raw materials, which can solve the problem of tight forest resources and increase the value of agricultural and forestry residues or by-products.
[0003] In the prior art, in the process of producing artificial boards, adhesives are added to the base material so that the adhesive bonds the base material and is pressed into shape by external force to obtain artificial boards. Therefore, the environmental friendliness of the glue determines the environmental friendliness of the board. At present, "trialdehyde glue" with formaldehyde as the reaction raw material, including urea-formaldehyde resin adhesive, phenolic resin adhesive and melamine resin adhesive, is still the main option for artificial board manufacturers. "Trialdehyde glue" artificial boards may have formaldehyde residues during the production process, and formaldehyde will also be emitted during the aging process, which often leads to excessive indoor formaldehyde content, irritating the respiratory tract, inducing leukemia, etc., seriously affecting human health.
[0004] As people's requirements for living environment continue to increase, the development of low formaldehyde emission or even formaldehyde-free decorative panels has gradually become the development direction of the wood-based panel industry. The adhesives for formaldehyde-free wood-based panels mainly include isocyanate glue, soybean glue and inorganic adhesives. Isocyanate glue is referred to as MDI glue. MDI glue has high reaction activity and good bonding strength. It is the most widely used and largest amount of formaldehyde-free glue, but the isocyanate group of MDI glue is too active, has high storage requirements and is easy to deteriorate; soybean glue is environmentally friendly and renewable, and is a green and sustainable adhesive, but it is limited by low bonding strength, easy to mold, and high production costs due to large glue mixing, so it is not widely used. Summary of the invention
[0005] In order to solve the problem of environmental pollution and limited application caused by the formaldehyde-free adhesive in the above-mentioned artificial board. The present invention provides a formaldehyde-free adhesive and its preparation method and application. The formaldehyde-free adhesive provided by the present invention has the advantages of cheap and easy availability of chemical raw materials, formaldehyde-free and environmentally friendly, high strength, repeatable thermal processing, stable chemical composition, easy storage, etc. The formaldehyde-free adhesive of the present invention has broad application prospects in the production of artificial boards, recycling of scraps and recycling of plates.
[0006] The first object of the present invention is to provide a formaldehyde-free adhesive, the raw materials for preparing the adhesive include a flow agent and a filler.
[0007] The flow agent is a compound containing epoxy groups.
[0008] The filler is a compound containing a carboxyl group and / or an acid anhydride group.
[0009] The molar amount of epoxy groups provided by the flow agent is 0.1 to 10 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
[0010] Preferably, the flow agent is one or more of glycidyl ethers, glycidyl esters, glycidyl amines and aliphatic epoxides.
[0011] The glycidyl ethers include, but are not limited to, glycidyl ether, 1,4-butanediol glycidyl ether, ethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, bisphenol A diglycidyl ether, bisphenol F diglycidyl ether and hydrogenated bisphenol A diglycidyl ether.
[0012] Preferably, the glycidyl esters include but are not limited to 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, resorcinol diglycidyl ether di(3,4-epoxycyclohexylmethyl) adipate, tetrahydrophthalic acid diglycidyl ester and cyclohexane-1,2-dicarboxylic acid diglycidyl ester.
[0013] Preferably, the glycidylamines include but are not limited to diglycidyl p-aminophenol and diaminodiphenylmethane tetraglycidylamine.
[0014] Preferably, the aliphatic epoxides include but are not limited to trimethylolpropane triglycidyl ether.
[0015] It should be noted that the flow agent used in the present invention is a compound containing an epoxy group, such as one or more of glycidyl ethers, glycidyl esters, glycidyl amines and aliphatic epoxides, and one of them, namely bisphenol A diglycidyl ether or bisphenol F diglycidyl ether, can be selected as the flow agent, or a mixture of two of them, hydrogenated bisphenol A diglycidyl ether and epoxidized soybean oil, can be selected as the flow agent, wherein the mass ratio of the mixture is not specifically limited. The molar amount of epoxy groups provided by the flow agent is 0.1 to 10 times the molar amount of carboxyl groups or / and anhydride groups provided by the filler.
[0016] The formaldehyde-free adhesive of the present invention is mainly composed of a flow agent and a filler. The epoxy group in the flow agent and the carboxyl group or anhydride group in the filler have low reactivity or basically do not react at room temperature. During the high-temperature mixing with biomass fiber or hot pressing with biomass fiber, epoxy ring-opening reaction, esterification reaction and transesterification reaction are carried out simultaneously between the epoxy group, carboxyl group or anhydride group and the functional group on the surface of the biomass fiber, and the formaldehyde-free adhesive and the biomass fiber are stably connected by chemical bonds. Therefore, the formaldehyde-free adhesive of the present invention has the advantages of high bonding strength and stable chemical properties, and in the process of preparing artificial boards using the formaldehyde-free adhesive provided by the present invention, the surface polarity of the formaldehyde-free adhesive is large after curing, and the interaction force between the formaldehyde-free adhesive and the biomass fiber in the artificial board is strong. The prepared artificial board has formaldehyde-free environmental protection, high static bending strength and good resistance to bending damage.
[0017] The filler used in the present invention is a compound containing a carboxyl group, and the filler includes but is not limited to maleic acid, fumaric acid, maleic anhydride, succinic acid, succinic anhydride, glutaric acid, glutaric anhydride, adipic acid, adipic anhydride, sebacic acid, phthalic acid, and phthalic anhydride. For example, adipic acid or succinic acid can be selected as the filler, or two of them, i.e., a mixture of adipic acid and succinic acid, can be selected as the filler, and the mass ratio of the two is not specifically limited.
[0018] Preferably, the formaldehyde-free adhesive further comprises an additive, wherein the additive is one or more of a catalyst, a diluent, a thixotropic agent, a flame retardant, a surfactant, a moisture-proof agent and a reinforcing and toughening agent. Preferably, the additive accounts for 1% to 20% of the total mass of the formaldehyde-free adhesive.
[0019] In order to promote the curing rate of the adhesive on the surface of the biomass fiber and the degree of reaction between the adhesive and the polar groups on the surface of the biomass fiber. The catalyst described in the present invention is one or more of an amine compound, a phosphorus compound and a metal compound, wherein one or two of zinc oxide, zinc borate, zinc acetate and zinc stearate are selected, and the amount of the catalyst is 0 to 2 times the molar amount of the epoxy group provided by the flow agent. It should be noted that in the present invention, the catalyst can be omitted, and the formaldehyde-free adhesive can be synthesized only by the flow agent and the filler.
[0020] Preferably, the metal compound includes but is not limited to zinc oxide, zinc borate, zinc hydroxide, zinc phosphate, zinc stearate, zinc citrate, zinc propionate, zinc acetylacetonate, zinc acetate, tetrabutyltin chloride, stannous octoate, dibutyltin diacetate, tin tetrachloride and dibutyltin dilaurate; the amine compound includes but is not limited to ethylenediamine, diethylenetriamine, triethylenediamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine, polyethylenepolyamine, isophoronediamine, aromatic amine, polyamide, polyetheramine, phenolic amine, amide, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,8-diazobispiro[5.4.0]-7-undecene and N-alkylmorpholine; the phosphorus compound includes zinc phosphide and trialkylphosphine.
[0021] Preferably, the present invention reduces the viscosity of the formaldehyde-free adhesive by adding a certain amount of diluent, facilitates the mixing of the formaldehyde-free adhesive and the biomass fiber, and improves the bonding between the formaldehyde-free adhesive and the biomass fiber. The diluent of the present invention is one or more of a monofunctional epoxy compound or a monocarboxyl compound, including but not limited to epichlorohydrin, glycidol, butyl glycidyl ether, phenyl glycidyl ether, benzyl glycidyl ether and o-cresyl glycidyl ether, and the mass fraction of the diluent is 0 to 5wt%. It should be noted that in the present invention, no diluent may be added, and the formaldehyde-free adhesive may be synthesized only by a flow agent and a filler.
[0022] Preferably, the thixotropic agent can significantly improve the construction performance of the formaldehyde-free adhesive. When the formaldehyde-free adhesive is stirred and mixed with the biomass fiber, the thixotropic agent quickly reduces the viscosity, which is convenient for stirring during mixing. After stopping stirring, the viscosity of the formaldehyde-free adhesive immediately increases, thereby enhancing the bonding effect with the biomass fiber. Preferably, the thixotropic agent is one or more of silicon dioxide, organic bentonite, asbestos, kaolin, attapulgite and hydroxyethyl cellulose, and the mass fraction of the thixotropic agent in the system is 0 to 5wt%. It should be noted that in the present invention, the thixotropic agent may not be added, and the formaldehyde-free adhesive may be synthesized only by a flow agent and a filler.
[0023] Preferably, the surfactant in the formaldehyde-free adhesive mainly includes reducing surface tension, enhancing solvent effect, improving wettability and permeability, and improving stability and dispersibility of the formaldehyde-free adhesive. Preferably, the surfactant is stearic acid, and the amount of the surfactant is 0-2wt%. It should be noted that in the present invention, the formaldehyde-free adhesive can be synthesized only by a flow agent and a filler without adding a surfactant.
[0024] Preferably, the present invention improves the flame retardant performance of the formaldehyde-free adhesive and biomass fiber during the mixing process under high temperature and high pressure by adding a certain amount of flame retardant to ensure safety in use. Preferably, the flame retardant is one or more of red phosphorus, graphite, carbon black, ammonium polyphosphate, aluminum hydroxide, melamine, antimony trioxide, melamine polyphosphate and phosphate, and the mass fraction of the flame retardant is 0 to 30wt%. It should be noted that in the present invention, surfactants may not be added, and the formaldehyde-free adhesive may be synthesized only by flow agents and fillers.
[0025] Preferably, the present invention reduces the cracking phenomenon during the bonding and curing process of the formaldehyde-free adhesive and the biomass fiber by adding a certain amount of a reinforcing and toughening agent, and reduces the internal stress of the adhesive joint, thereby improving the strength of the formaldehyde-free adhesive and improving the toughness of the formaldehyde-free adhesive. Preferably, the reinforcing and toughening agent is one of glass fiber, carbon fiber, polymer fiber, nano-silica and hollow glass microspheres, and the amount of the reinforcing and toughening agent is 0 to 30wt%. It should be noted that in the present invention, a surfactant may not be added, and the formaldehyde-free adhesive may be synthesized only by a flow agent and a filler.
[0026] A second object of the present invention is to provide a method for preparing the above-mentioned formaldehyde-free binder, comprising the following steps:
[0027] According to the ratio of each raw material for preparing the formaldehyde-free adhesive, the raw materials are mixed to obtain the formaldehyde-free adhesive.
[0028] The raw materials for preparing the formaldehyde-free adhesive include a flow agent, a filler and an additive. During the mixing process of the raw materials, the epoxy groups in the flow agent and the carboxyl groups or anhydride groups in the filler have low reaction activity or basically do not react at room temperature, and the formaldehyde-free adhesive is obtained by combining the molecular forces between the raw materials.
[0029] Preferably, in the preparation process of the formaldehyde-free binder, the flow agent, the filler and the additive are directly blended in a container, and after blending, the components interact with each other by intermolecular forces to form the formaldehyde-free adhesive. The present invention does not specifically limit the blending equipment, including but not limited to a stirrer, a ball mill, a grinder, a sand mill, a single / twin screw extruder, an internal mixer and an open mixer.
[0030] Adhesives play an important role in the artificial board manufacturing industry. In the production process, the substrate is bonded by the adhesive and pressed into shape by external force to obtain artificial boards. In the prior art, when preparing artificial boards, the adhesives used are mainly inorganic gelling materials such as cement and gypsum. Although they have the advantages of high strength and flame retardancy, the prepared boards have high density and heavy weight, which also limits their application in the artificial board industry. In addition, in the prior art, whether it is "trialdehyde glue", MDI glue or formaldehyde-free glue of inorganic adhesives, the curing process is irreversible, which makes it difficult to recycle and reuse the artificial boards produced using the adhesives, which is easy to cause waste and pollute the environment.
[0031] The third object of the present invention is to provide a method for preparing an artificial board using the above-mentioned formaldehyde-free binder. During the board making process, the formaldehyde-free adhesive is combined with the surface of the biomass fiber, and the epoxy group and carboxyl group or anhydride group in the formaldehyde-free adhesive directly and fully react with the ester group, carboxyl group and hydroxyl group of the biomass fiber itself at high temperature to form new ester bonds, ether bonds and hydroxyl groups. The formaldehyde-free adhesive is completely cured on the surface of the biomass fiber through covalent bonds and electrostatic effects, and then a hot pressing operation is performed to make the artificial board. The specific steps are:
[0032] S1. Glue mixing: evenly mix the formaldehyde-free adhesive and the biomass fiber to form glue-mixed fiber.
[0033] S2. Board making: The mixed rubber fibers are hot-pressed and solidified under heating and pressurizing conditions to obtain artificial boards.
[0034] Preferably, in the preparation process of the rubber-mixed fiber in S1 of the present invention, the biomass fiber can be blended with the formaldehyde-free adhesive, or the flow agent, filler and additive are added to the biomass fiber and then blended. There is no specific requirement for the blending equipment, which can be a rubber mixer or a material mixer; there is no specific restriction on the mixing temperature, which is room temperature to 300°C, and more preferably between 120°C and 220°C; there is no specific restriction on the mixing time, which is usually 10min to 300min.
[0035] Preferably, the biomass fiber in S1 of the present invention is one or more of wood, plant straw, bamboo and reed. Preferably, the wood includes but is not limited to wood, branches and shrubs, the plant straw includes but is not limited to corn straw, wheat straw, bean stalk, cotton stalk, sunflower stalk, coconut palm, rice husk and hay, the bamboo includes but is not limited to bamboo and chaff, and the reed includes reed and Phragmites australis. The form of the biomass raw material used for the preparation of artificial boards is not specifically limited, including but not limited to flakes, particles, fibers and powder.
[0036] Preferably, the feed ratio between the formaldehyde-free adhesive and the biomass fiber in S1 of the present invention is not specifically limited and is adjusted according to the fiber size and the formula of the formaldehyde-free adhesive. Generally, the amount of the formaldehyde-free adhesive is 2wt% to 30wt% of the mass of the biomass fiber, preferably 5wt% to 10wt%.
[0037] Preferably, the heating temperature in the S2 hot pressing curing process of the present invention is 120°C to 300°C, more preferably 120°C to 220°C. The pressure is not specifically limited and is between 0.1MPa and 10MPa, preferably 1MPa to 5MPa. The type and model of the hot pressing equipment used are not specifically limited.
[0038] Preferably, the boards and scraps of the artificial boards produced in S2 can be recycled and crushed into a loose state, and then the artificial boards can be obtained again by repeating S2 without adding glue or adding less glue. The recycled materials can be directly subjected to S2 operation, or can be subjected to S1 first and then S2, wherein the amount of glue mixed when performing S1 is not specifically limited.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The formaldehyde-free adhesive of the present invention uses a flow agent and a filler as main raw materials for preparation, wherein the epoxy group in the flow agent and the carboxyl group or anhydride group in the filler have low reactivity or basically do not react at room temperature, and the formaldehyde-free adhesive is formed by combining the molecular forces between the raw materials. The formaldehyde-free adhesive has high bonding strength, because the epoxy group and the carboxyl group or anhydride group in the formaldehyde-free adhesive can directly react and couple with the surface group of the biomass fiber, the formaldehyde-free adhesive has large surface polarity after curing, strong interaction with the biomass fiber, and high self-strength after curing; at the same time, the carboxyl group or anhydride group in the formaldehyde-free adhesive has low reactivity or basically does not react at room temperature, the physical and chemical properties are stable, not easy to deteriorate, and it does not solidify after being stored at room temperature for 3 months, and there is no need to isolate water and oxygen during the storage process. Therefore, the formaldehyde-free adhesive prepared by the present invention has the advantages of high bonding strength, stable physical and chemical properties and not easy to deteriorate, while avoiding the problem of adding a large amount of formaldehyde-free adhesive during use, thereby reducing the production cost of artificial boards and facilitating promotion for large-scale production and use.
[0041] In the process of preparing the artificial board with the formaldehyde-free adhesive of the present invention, the epoxy group in the flow agent and the carboxyl group and the acid anhydride in the filler directly and fully react with the ester group, carboxyl group and hydroxyl group of the biomass fiber itself at high temperature, and simultaneously carry out the ring-opening reaction between the epoxy and the carboxyl group, the acid anhydride or the hydroxyl group, and the exchange reaction between the ester group and the ester group or the ester group and the hydroxyl group, and finally form a covalent bond between the biomass fiber and the formaldehyde-free adhesive interface to improve the bonding strength, and at the same time, the formaldehyde-free adhesive changes from soft to hard and from weak to strong after thermal curing, and finally forms an artificial board composed of the formaldehyde-free adhesive-biomass fiber composite system. In addition, the formaldehyde-free adhesive can be cured on the biomass fiber in advance in the glue mixing stage, reducing the residence time of the artificial board in the continuous hot pressing stage and improving production efficiency. More importantly, the formaldehyde-free adhesive with a complete curing reaction is still reversible. After heating again, the formaldehyde-free adhesive will melt again and can continue to bond the biomass fibers together for board production. The scraps produced by cutting in the later stage of board making can be re-hot-pressed into boards without adding glue, which is conducive to the secondary utilization of artificial board waste, saving resources and protecting the environment. These are unique properties that existing artificial board adhesives such as urea-formaldehyde glue, phenol-formaldehyde glue, melamine glue, and MDI glue cannot achieve. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The formaldehyde-free adhesive prepared in Example 1 of the present invention.
[0043] Figure 2 This is the wheat straw board synthesized in Application Example 1 of the present invention.
[0044] Figure 3 This is the reed board synthesized in Application Example 3 of the present invention.
[0045] Figure 4 The broken bamboo chaff of Application Example 5 of the present invention.
[0046] Figure 5 This is the bamboo chaff board synthesized according to Application Example 5 of the present invention. DETAILED DESCRIPTION
[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings. In the description of the present invention, unless otherwise specified, the reagents used are all commercially available, and the methods used are all conventional techniques in the art.
[0048] The present invention provides a method for preparing a formaldehyde-free adhesive for preparing artificial panels, which is further described below through specific examples.
[0049] Example 1
[0050] This embodiment provides a formaldehyde-free adhesive for preparing artificial boards.
[0051] The raw materials for preparing the formaldehyde-free adhesive of this embodiment are composed of a flow agent, a filler, a catalyst and a diluent. In this embodiment, bisphenol F diglycidyl ether is used as a flow agent, succinic acid is used as a filler, zinc stearate and zinc borate are used as catalysts, and glycidol is used as a diluent.
[0052] In this embodiment, the mass ratio of bisphenol F diglycidyl ether and succinic acid is limited to 100:100, so that the molar amount of epoxy groups provided by the flow agent is 1 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
[0053] The formaldehyde-free adhesive of the present embodiment is prepared by the following steps:
[0054] According to the mass ratio of bisphenol F diglycidyl ether, succinic acid, zinc stearate, zinc borate and glycidol of 100:100:1:5:5, bisphenol F diglycidyl ether, succinic acid, zinc stearate, zinc borate and glycidol are stirred at room temperature for 10 minutes. After stirring evenly, the solid components are fully ground using a ball mill and mixed with the liquid to form a paste-like fluid, which is the formaldehyde-free adhesive.
[0055] Example 2
[0056] This embodiment provides a formaldehyde-free adhesive for preparing artificial boards.
[0057] The raw materials for preparing the formaldehyde-free adhesive of this embodiment are composed of a flow agent, a filler, a catalyst, a diluent and a plasticizer. In this embodiment, hydrogenated bisphenol A diglycidyl ether is used as a flow agent, adipic acid and succinic acid are used as fillers, zinc acetate is used as a catalyst, phenyl epoxy ether is used as a diluent, and epoxy soybean oil is used as a plasticizer.
[0058] In this embodiment, the mass ratio of hydrogenated bisphenol A diglycidyl ether, adipic acid and succinic acid is limited to 100:50:50, so that the molar amount of epoxy groups provided by the flow agent is 1 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
[0059] The formaldehyde-free adhesive of the present embodiment is prepared by the following steps:
[0060] According to the mass ratio of hydrogenated bisphenol A diglycidyl ether, adipic acid, succinic acid, zinc acetate, phenyl epoxy ether and epoxy soybean oil of 100:50:50:5:5:10, hydrogenated bisphenol A diglycidyl ether, epoxy soybean oil, adipic acid, succinic acid, zinc acetate and phenyl epoxy ether are stirred at room temperature for 10 minutes. After stirring evenly, a grinder is used to fully grind and mix the solid and liquid components to form a paste-like viscous substance, which is the formaldehyde-free adhesive.
[0061] Example 3
[0062] This embodiment provides a formaldehyde-free adhesive for preparing artificial boards.
[0063] The raw materials for preparing the formaldehyde-free adhesive of this embodiment are composed of a flow agent, a filler, a catalyst, a diluent and a plasticizer. In this embodiment, bisphenol A diglycidyl ether is used as a flow agent, adipic acid and succinic acid are used as fillers, and bicyclic amidine is used as a catalyst.
[0064] In this embodiment, the mass ratio of bisphenol A diglycidyl ether, adipic acid and succinic acid is limited to 100:50:50, so that the molar amount of epoxy groups provided by the flow agent is 1 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
[0065] The formaldehyde-free adhesive of the present embodiment is prepared by the following steps:
[0066] According to the mass ratio of bisphenol A diglycidyl ether, adipic acid, succinic acid and bicyclic amidine of 100:50:50:5, the chemical name of bicyclic amidine is 1,8-diazobispiro[5.4.0]-7-undecene. Bisphenol A diglycidyl ether, adipic acid, succinic acid and bicyclic amidine are stirred at room temperature for 10 minutes. After stirring evenly, a sand mill is used to fully grind and mix the solid and liquid components to form a toothpaste-like viscous substance, which is the formaldehyde-free adhesive.
[0067] Example 4
[0068] This embodiment provides a method for preparing a formaldehyde-free adhesive for preparing artificial boards.
[0069] The raw materials for preparing the formaldehyde-free adhesive of this embodiment are composed of a flow agent, a filler, a catalyst, a diluent and a plasticizer. In this embodiment, bisphenol A diglycidyl ether is used as a flow agent, adipic acid is used as a filler, and zinc oxide and zinc acetate are used as catalysts.
[0070] In this embodiment, the mass ratio of bisphenol A diglycidyl ether and adipic acid is limited to 100:100, so that the molar amount of epoxy groups provided by the flow agent is 1 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
[0071] The formaldehyde-free adhesive of the present embodiment is prepared by the following steps:
[0072] According to the mass ratio of bisphenol A diglycidyl ether, adipic acid, zinc oxide and zinc acetate of 100:100:10:5, bisphenol A diglycidyl ether, adipic acid, zinc oxide and zinc acetate are stirred at room temperature for 10 minutes. After stirring evenly, a grinder is used to fully grind and mix the solid and liquid components to form a paste-like viscous substance, which is the formaldehyde-free adhesive.
[0073] Example 5
[0074] This embodiment provides a method for preparing a formaldehyde-free adhesive for preparing artificial boards.
[0075] The raw materials for preparing the formaldehyde-free adhesive of this embodiment are composed of a flow agent, a filler, a catalyst, a diluent, a thixotropic agent and a flame retardant. Among them, this embodiment uses bisphenol A diglycidyl ether as a flow agent, succinic acid as a filler, zinc oxide as a catalyst, butyl glycidyl ether as a diluent, hydroxyethyl cellulose as a thixotropic agent, and aluminum hydroxide as a flame retardant.
[0076] In this embodiment, the mass ratio of bisphenol A diglycidyl ether and succinic acid is limited to 100:100, so that the molar amount of epoxy groups provided by the flow agent is 1 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
[0077] The formaldehyde-free adhesive of the present embodiment is prepared by the following steps:
[0078] According to the mass ratio of bisphenol A diglycidyl ether, succinic acid, zinc oxide, hydroxyethyl cellulose, butyl glycidyl ether and aluminum hydroxide of 100:100:10:1:5:10, bisphenol A diglycidyl ether, succinic acid, zinc oxide, hydroxyethyl cellulose, butyl glycidyl ether and aluminum hydroxide are stirred at room temperature for 10 minutes. After stirring evenly, the solid and liquid components are fully ground and mixed using a grinder to form a paste-like viscous material to obtain a formaldehyde-free adhesive.
[0079] Example 6
[0080] This embodiment provides a formaldehyde-free adhesive for preparing artificial boards.
[0081] The difference between this embodiment and embodiment 1 is:
[0082] In this embodiment, the molar amount of epoxy groups provided by the flow agent is 0.1 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
[0083] Example 7
[0084] This embodiment provides a method for preparing a formaldehyde-free adhesive for preparing artificial boards.
[0085] The difference between this embodiment and embodiment 1 is:
[0086] In this embodiment, the molar amount of epoxy groups provided by the flow agent is 10 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
[0087] The formaldehyde-free adhesives prepared in Examples 1 to 7 were respectively used to prepare artificial boards.
[0088] Application Example 1
[0089] This application embodiment provides a man-made board prepared based on a formaldehyde-free adhesive.
[0090] S1. Glue mixing: using a crusher to crush wheat straw into wheat fine fibers with a length of about 1 cm and a width of 2 mm, the formaldehyde-free adhesive prepared in Example 1 and the wheat fine fibers are mixed in a glue mixer for 10 min, wherein the amount of the formaldehyde-free adhesive is 5% of the mass of the wheat fine fibers, and the temperature is controlled at 80° C. during the glue mixing process to obtain glue-mixed fibers.
[0091] S2. Board making: The rubber-mixed fibers obtained in S1 are placed in a hot press mold, hot-pressed at 180° C. for 30 min at a pressure of 3 MPa, and a man-made board is obtained after demoulding, which is recorded as wheat straw board.
[0092] Application Example 2
[0093] This application embodiment provides a man-made board prepared based on a formaldehyde-free adhesive.
[0094] S1. Glue mixing: Use a crusher to break corn stalks into corn fine fibers with a length of about 3 cm and a width of 0.5 mm. Mix the formaldehyde-free adhesive prepared in Example 2 and the corn fine fibers in a glue mixer for 10 minutes, wherein the amount of formaldehyde-free adhesive is 2% of the mass of the corn fine fibers. Then, place the mixture in a heating chamber and heat it at 160° C. for 1 hour to completely cure the formaldehyde-free adhesive on the surface of the corn fine fibers to form glue-mixed fibers.
[0095] S2. Board making: The rubber-mixed fibers obtained in S1 are placed in a hot press mold, hot-pressed at 180° C. for 3 min at a pressure of 3 MPa, and the artificial board is obtained after demoulding, which is recorded as corn straw board.
[0096] Application Example 3
[0097] This application embodiment provides a man-made board prepared based on a formaldehyde-free adhesive.
[0098] S1. Glue mixing: Use a crusher to crush reed straw into reed fine fibers with a length of about 1 cm and a diameter of about 0.1 mm, mix the formaldehyde-free adhesive prepared in Example 3 and the reed fine fibers in a glue mixer for 10 min, wherein the amount of formaldehyde-free adhesive is 5% of the mass of the reed fine fibers, and then place the mixture in a heating chamber and heat at 160° C. for 1 h to completely cure the formaldehyde-free adhesive on the surface of the reed fine fibers to form glue-mixed fibers.
[0099] S2. Board making: The rubber-mixed fibers obtained in S1 are placed in a hot press mold, hot-pressed at 180° C. for 3 min at a pressure of 3 MPa, and an artificial board is obtained after demoulding, which is recorded as reed board.
[0100] Application Example 4
[0101] This application embodiment provides a man-made board prepared based on a formaldehyde-free adhesive.
[0102] S1. Glue mixing: Use a crusher to crush poplar branches into solid wood particles with a size of about 1 cm, mix the formaldehyde-free adhesive prepared in Example 4 and the solid wood particles in a glue mixer for 10 minutes, wherein the amount of formaldehyde-free adhesive is 5% of the mass of the solid wood particles, and then place in a heating chamber for thermal curing at 180°C for 30 minutes at a pressure of 3 MPa to obtain glue-mixed fibers.
[0103] S2. Board making: The mixed rubber fiber obtained in S1 is continuously hot-pressed in a continuous hot press for about 3 minutes. After demoulding, a formaldehyde-free artificial board is obtained, which is recorded as a solid wood particle board.
[0104] Application Example 5
[0105] This application embodiment provides a man-made board prepared based on a formaldehyde-free adhesive.
[0106] S1. Glue mixing: The scraps produced in the bamboo processing process are crushed into bamboo chaff using a crusher, and the formaldehyde-free adhesive prepared in Example 5 and the bamboo chaff are mixed in a mixer for 10 minutes, wherein the amount of the formaldehyde-free adhesive is 15% of the mass of the bamboo chaff. The fibers are then placed in a heating chamber for heating and curing at 160° C. for 30 minutes to obtain glue-mixed fibers.
[0107] S2. Board making: The mixed rubber fiber obtained in S1 is hot pressed in a hot press at a temperature of 180° C., a pressure of 3 MPa, and a residence time of about 30 min. After demoulding, an artificial board is obtained, which is recorded as bamboo bran board.
[0108] Application Example 6
[0109] This application embodiment provides a man-made board prepared based on a formaldehyde-free adhesive.
[0110] The bamboo chaff board obtained in Example 10 was crushed and processed into small particles with a particle size of <5 mm. The small particles were placed in a mold and preheated at 180°C for 30 minutes, and then hot pressed at a temperature of 180°C, a pressure of 3 MPa, and a residence time of about 30 minutes. After demolding, the repeatedly processed artificial board was obtained, which was recorded as the repeatedly processed bamboo chaff board.
[0111] Application Example 7
[0112] This application embodiment provides a man-made board prepared based on a formaldehyde-free adhesive.
[0113] S1. Glue mixing: using a crusher to crush wheat straw into wheat fine fibers with a length of about 1 cm and a width of 2 mm, the formaldehyde-free adhesive prepared in Example 6 and the wheat fine fibers are mixed in a glue mixer for 300 min, wherein the amount of the formaldehyde-free adhesive is 30% of the mass of the wheat fine fibers, and the temperature is controlled at room temperature during the glue mixing process to obtain glue-mixed fibers.
[0114] S2. Board making: The rubber-mixed fibers obtained in S1 are placed in a hot press mold, hot-pressed at 120° C. for 30 min at a pressure of 0.1 MPa, and a man-made board is obtained after demoulding, which is recorded as wheat straw board.
[0115] Application Example 8
[0116] This application embodiment provides a man-made board prepared based on a formaldehyde-free adhesive.
[0117] S1. Glue mixing: The wheat straw is crushed into wheat fine fibers with a length of about 1 cm and a width of 2 mm using a crusher, and the formaldehyde-free adhesive prepared in Example 7 and the wheat fine fibers are mixed in a glue mixer for 10 min, wherein the amount of the formaldehyde-free adhesive is 5% of the mass of the wheat fine fibers. The temperature is controlled at 300° C. during the glue mixing process to obtain glue-mixed fibers.
[0118] S2. Board making: The rubber-mixed fibers obtained in S1 are placed in a hot press mold, hot-pressed at 300° C. for 30 min at a pressure of 10 MPa, and a man-made board is obtained after demoulding, which is recorded as wheat straw board.
[0119] The difference between this application example and application example 1 is that the formaldehyde-free adhesive used is prepared in example 6, and the amount of formaldehyde-free adhesive used is 30% of the mass of wheat fine fiber.
[0120] Experimental testing
[0121] Figure 1 This is the formaldehyde-free adhesive prepared in Example 1. As can be seen from the figure, the formaldehyde-free adhesive has a certain fluidity.
[0122] After the artificial boards prepared in Application Examples 1 to 8 were cut into corresponding shapes, the surface morphology and performance tests of formaldehyde emission, density and static bending strength were carried out, wherein the formaldehyde emission was tested according to the standard of GB / T39600-2021, and the density and static bending strength were tested according to the standard of GB / T 11718-2021. The data results of formaldehyde emission, density and static bending strength are shown in Table 1 below. The surface morphology is as follows Figure 2 to Figure 5 shown.
[0123] Table 1 Formaldehyde emission, density and static bending strength of the artificial boards prepared in Application Examples 1 to 6
[0124]
[0125] It can be seen from Table 1 that after the formaldehyde test of the artificial boards prepared by using Examples 1 to 6, the measured results are all less than 0.025 mg / m 3 , reaching ENF level, indicating that the prepared artificial board meets the ENF level formaldehyde-free property.
[0126] After the density test of the artificial boards prepared by using Examples 1 to 6, the density value of the artificial boards prepared by using Examples 1 to 4 is 550Kg / m 3 ~880Kg / m 3 , which is a medium density board with good strength and toughness. The density of the artificial board prepared in Example 10 is 1120Kg / m 3 , greater than 880Kg / m 3 , is a high-density board with high strength but poor toughness.
[0127] After the static bending strength test of the artificial boards prepared by using Examples 1 to 6, the static bending strengths are all greater than 22Mpa, indicating that the prepared artificial boards have strong resistance to bending damage and good quality. The static bending strengths of the bamboo chaff board prepared in Example 5 and the repeatedly processed bamboo chaff board prepared in Example 6 are 24Mpa and 22Mpa respectively, indicating that after the bamboo chaff board prepared in Example 5 is repeatedly hot-pressed, the static bending strength of the repeatedly processed bamboo chaff board is maintained at 22Mpa, and the resistance to bending damage of the bamboo chaff board remains stable. It is shown that the artificial board prepared by this example has formaldehyde-free and repeatable hot pressing properties, and the quality and performance of the artificial board are not changed while achieving repeated hot pressing.
[0128] Compared with the wheat straw board synthesized in Application Example 1, the wheat straw board synthesized in Application Example 7 has a formaldehyde emission, density and static bending strength effect of 95%; the wheat straw board synthesized in Application Example 8 has a formaldehyde emission, density and static bending strength effect of 95%.
[0129] Figure 2 This is the wheat straw board synthesized in Application Example 1. As can be seen from the figure, the straws in the wheat straw board are obvious and closely arranged.
[0130] Figure 3 This is the reed board synthesized in Application Example 3. As can be seen from the figure, the broken straw fibers in the reed board are obvious and closely arranged.
[0131] Figure 4 The bamboo chaff is crushed in Application Example 5. As can be seen from the figure, the bamboo chaff produced after the bamboo is crushed is in the form of solid particles.
[0132] Figure 5 The bamboo chaff board synthesized in Application Example 5. As can be seen from the figure, the bamboo chaff board after hot pressing the solid bamboo chaff particles using a formaldehyde-free adhesive is compact and dense.
[0133] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A formaldehyde-free adhesive for preparing artificial boards, characterized in that: The raw materials for preparing the formaldehyde-free adhesive include a flow agent and a filler; The flow agent is a compound containing epoxy groups; The filler is a compound containing a carboxyl group and / or an anhydride group; The molar amount of epoxy groups provided by the flow agent is 0.1 to 10 times the molar amount of carboxyl groups and / or anhydride groups provided by the filler.
2. The formaldehyde-free adhesive according to claim 1, characterized in that: The flow agent is one or more of glycidyl ethers, glycidyl esters, glycidyl amines and aliphatic epoxides; The filler is one or more of maleic acid, fumaric acid, maleic anhydride, succinic acid, succinic anhydride, glutaric acid, glutaric anhydride, adipic acid, adipic anhydride, sebacic acid, phthalic acid and phthalic anhydride.
3. The formaldehyde-free adhesive according to claim 1, characterized in that: The raw materials for preparing the formaldehyde-free adhesive further include additives, and the additives are one or more of a catalyst, a diluent, a thixotropic agent, a flame retardant, a surfactant, a moisture-proof agent, and a reinforcing and toughening agent; The additive accounts for 1% to 20% of the total mass of the formaldehyde-free adhesive.
4. A method for preparing the formaldehyde-free adhesive according to any one of claims 1 to 3, characterized in that: The following steps are involved: According to the ratio of each raw material for preparing the formaldehyde-free adhesive, the raw materials are mixed to obtain the formaldehyde-free adhesive.
5. Use of the formaldehyde-free adhesive according to any one of claims 1 to 4 in the preparation of artificial boards.
6. The use according to claim 5, wherein the artificial board is prepared by the following steps: Glue mixing: evenly mix the formaldehyde-free adhesive and biomass fiber to form glue-mixed fiber; Board making: The mixed rubber fibers are hot-pressed and solidified under heating and pressurizing conditions to obtain artificial boards.
7. The use according to claim 6, characterized in that: The biomass fibers are one or more of wood, plant straw, bamboo and reed.
8. The use according to claim 6, characterized in that: The dosage of the formaldehyde-free adhesive is 2wt% to 30wt% of the mass of the biomass fiber.
9. The use according to claim 6, characterized in that: The temperature during the glue mixing is from room temperature to 300°C.
10. The use according to claim 6, characterized in that: The heating temperature is 120° C. to 300° C., and the pressurizing pressure is 0.1 MPa to 10 MPa.
Citation Information
Cited By
Flame-retardant wood board as well as preparation method and application thereof
CN120326725A
Flame-retardant wood-based panel and preparation method and application thereof
CN120326725B